The Emerging Role of T-Cell Immunoglobulin Mucin-3 in Breast Cancer: A Promising Target For Immunotherapy - Cong, Yizi; Liu, Jing; Chen, Gang; Qiao, Guangdong (Frontiers in Oncology, 2021)
Cancer treatment through immune checkpoint receptor blockade has made significant advances in the recent years. However, resistance to the current immune checkpoint inhibitors (ICIs) has been observed in many patients, who consequently do not respond to these treatments. T-cell immunoglobulin mucin-3 (Tim-3) is a novel immune checkpoint molecule emerging as a potential therapeutic target for cancer immunotherapy. Epidemiologic findings reveal that genetic polymorphisms in the Tim-3 gene are associated with increased susceptibility to breast cancer. In patients with breast cancer, Tim-3 is expressed both on immune and tumor cells. Accumulating evidence demonstrates that Tim‐3 can notably affect breast cancer treatment outcome and prognosis. Therefore, Tim‐3 is being regarded as a high-potential target for improving breast cancer therapy. In this review, we summarize the role of Tim‐3 in breast cancer and the regulation mechanisms of Tim-3 to furnish evidence for future research and therapy.